Differences in the Force Velocity Mechanical Profile and the Effectiveness of Force Application During Sprint-Acceleration Between Sprinters and Hurdlers - Stavridis, Ioannis; Smilios, Ilias; Tsopanidou, Angela; Economou, Theodosia; Paradisis, Giorgos (Frontiers in Sports and Active Living, 2019)
This cross-sectional study aimed to compare the horizontal and vertical force-velocity profile between female sprinters and hurdlers. Twelve high-level athletes (6 sprinters and 6 hurdlers) participated in this investigation. The testing procedures consisted of two maximal 40-m sprints and five to six vertical jumps with additional loads. For the sprint-acceleration performance, the velocity-time data, recorded by a high-speed camera, was used to calculate the variables of the horizontal F-V profile (theoretical maximal values of force [HZT-F0], velocity [HZT-V0], power [HZT-Pmax], the proportion of the theoretical maximal effectiveness of force application in the antero-posterior direction [RFmax], and the rate of decrease in the ratio of horizontal force [DRF]). The best trial of each vertical jumping condition, obtained by an optical measurement system, was used to determine the components of the vertical F-V profile (theoretical maximal values of force [VTC-F0], velocity [VTC-V0], and power [VTC-Pmax]). The female sprinters showed higher statistical differences for HZT-Pmax (2.46 ± 0.67, d = 2.1, p = 0.004), HZT-V0 (0.45 ± 0.18, d = 1.4, p = 0.03), and RFmax% (2.9 ± 0.9%, d = 1.8, p = 0.01) than female hurdlers. No statistical differences were observed for HZT-F0 (0.69 ± 0.3, d = 1.15, p = 0.07), DRF% (−0.24 ± 0.4%, d = 0.3, p = 0.62), VTC-F0 (−2.1 ± 3.8, d = 0.3, p = 0.59), VTC-V0 (0.25 ± 0.31, d = 0.5, p = 0.45), and VTC-Pmax (1.75 ± 2.5, d = 0.4, p = 0.5). Female sprinters are able to apply higher horizontally-oriented forces onto the ground during the acceleration phase than female hurdlers.